Multi-Frequency and Single-Crystal EPR on V4+ in W-Doped β-Vanadyl(V) Phosphate: Hyperfine Coupling- and g-Tensor Values and Orientation - NejatyJahromy, Yaser; Roy, Subrata Chandra; Glaum, Robert; Schiemann, Olav (Applied magnetic resonance, 2021)
Different structure types of vanadyl(V) orthophosphate [i.e. (V V ≡O) 3+ orthophosphate] have been subjects of research due to their catalytic activity in the oxidation of n -butane to maleic anhydride. Electron paramagnetic resonance (EPR) spectroscopy can be exploited to elucidate the electronic structure of such compounds. When tuning the oxidation state of vanadium in (V 1-x W x )OPO 4 , X-band EPR spectra have confirmed the presence of paramagnetic V 4+ ions. However, some of the features in these spectra could not be explained. Here, powder samples of β -(V IV 0.01 V V .98 W VI .01 )OPO 4 are investigated at S-, X- and Q- band, along with X-band EPR measurements on single crystals. Thereby, the discrepancies between the spectra and their simulations could be resolved. In particular, it could be shown that the g and A tensors are not coaxial. The resulting consistent EPR picture and the refined paramagnetic parameters are reported. The work underlines the indispensability of a multi-frequency approach in EPR for unequivocal conclusions.